PEMBELAJARAN BAHASA ARAB BERBASIS OUTDOOR LEARNING DI SMA SWASTA (SMAS) MUHAMMADIYAH TOBOALI - Umar Rizki Fitroni Merciandy; Khizanatul Hikmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the process of outdoor learning-based Arabic learning (OL) at SMAS Muhammadiyah Toboali and students' responses to outdoor learning-based Arabic learning. The method used is descriptive with a qualitative approach. Research data were collected through observation, interviews, and documentation. The results of this study: 1) Arabic Language Learning Process based on outdoor learning at SMAS Muhammadiyah Toboali, as follows: a. Learning planning, Preparing lesson plans and determining OL learning locations. b. The implementation of learning, learning is carried out using the outdoor learning method with isim dhomir material presented with songs. c. Evaluate learning, parse student learning outcomes and follow up. 2) Response from students and class X students of SMAS Muhammadiyah Toboali after participating in the implementation of outdoor learning methods which showed that students became more motivated in participating in Arabic language learning.